Adsorption cooling system employing activated carbon/ hfc410a adsorption pair - Askalany, A. (Asian Research Publishing Network, 2016)
This paper presents operation conditions and performance of an adsorption cooling system employing activated carbon powder (ACP)/HFC410a adsorption pair. The system has been modelled and simulated numerically and the effect of changing the operating conditions has been studied. The system is driven by a low grade heat source of temperature below 80Â°C and effectively exploits solar heat and/or waste sources to drive the system. Results indicate that ACP/HFC410A is able to achieve specific cooling power (SCP) and coefficient of performance (COP) values of about 0.2 kW/kg and 0.3 respectively at 350 K regeneration temperature and 387 K evaporator temperature. Â©2006-2016 Asian Research Publishing Network (ARPN).